Health information management of older, multimorbid patients in German primary care: feasibility and first results of the outcome measures of a cluster-randomised controlled pilot trial – HYPERION-TransCare - Astrid-Alexandra Klein; Maria Hanf; Truc Sophia Dinh; Franziska Brosse; Jenny Petermann; Steve Piller; Sylvia Schulz-Rothe; Lena Schäfer; Karola Mergenthal; Hanna M. Seidling; Sophia Klasing; Nina Timmesfeld; et al. (BMC Primary Care)
Abstract Background Availability of information at the interface of outpatient and inpatient care remains an important and inadequately resolved issue in Germany and beyond. As a vulnerable group with complex care needs, older patients, mostly multimorbid, are especially affected by the consequences. This trial tested the feasibility and implementability of a complex intervention which aimed at improving the availability of health information among patients and different healthcare providers. Methods The prospective two-arm blinded pilot cRCT was accompanied by an explorative mixed-methods process evaluation. Over a period of six months in 2022, general practitioner (GP) practices in Germany with patients (≥ 65, multimorbid, polypharmacy) participated in testing the implementation of the intervention and the trial design (intervention (IG) vs control group (CG)). Here, the focus is on the feasibility and exploratory results of the primary (combined endpoint of hospitalisation, falls and mortality) and secondary outcome measures (improving GP practices’ and patients’ knowledge of health-related resource use (FIMA), as well as improving patients’ Health Literacy (HLQ-G) and Satisfaction with Medication Information (SIMS-D)). Data were analysed according to the intention to treat principle. Results Twelve GP practices were randomised (6 per IG/CG). Of 159 patients invited, 93 were included in the analyses (52 IG/41 CG). At t0 and t1, only few self-reported data from patients (5 resp. 10) or from the GP questionnaire (resp. 0) were missing. At least one survey perspective was available for each patient at both survey times. Overall, there were few missing items in the questionnaires, so the scores could not be calculated in 4-18% of cases (primary combined endpoint 9%), and there were no single items with increased missing values (n = 0 to 7). The concordance of the hospitalisation data from patients and GP practices was about 80%. Exploratory analyses showed no effects of the intervention on primary or secondary outcome measures. Conclusions The primary combined endpoint was feasible. The secondary outcomes and survey methods used also proved feasible for GP practices and older multimorbid patients, with low missing rates. However, there was no hint of the influence of the intervention in the study groups in the explorative analyses. Trial registration The trial was registered in the DRKS German Clinical Trials Register: registration number DRKS00027649 (date: 19.01.2022); http://www.drks.de/DRKS00027649 .